Analisa Keuangan PT. Medikaloka Hermina Tbk : Evaluasi Kinerja Keuangan dan Perbandingan Dengan PT. Siloam Internasional Hospitals (SILO) - Dewi Inggriyani; Alfiatur Rizki; Irma Nurfauzia; Yusni Sulastri; Nurhasanah Dewi; Yanuar Ramadhan (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
PT Medikaloka Hermina Tbk is one of the largest private hospital networks in Indonesia, continuously expanding to meet the challenges of the healthcare service industry. This study analyzes the company’s financial performance from 2022 to 2024, focusing on the statement of financial position, income statement, and cash flow statement. The main issue addressed is the high operational costs affecting financial efficiency and sustainability. The study aims to evaluate the company’s ability to generate profit, manage assets and liabilities, and maintain financial stability. The method employed involves financial statement analysis and performance comparison with its main competitor, Siloam Hospitals. The findings reveal a significant increase in revenue, reflecting successful expansion and enhanced service capacity. Despite rising operational costs and long-term liabilities, Hermina has maintained healthy profit margins and asset utilization efficiency. Compared to Siloam, Hermina demonstrates greater effectiveness in generating net income relative to revenue. In conclusion, PT Medikaloka Hermina Tbk is in a strong financial position, although debt management and operational efficiency must continue to improve to ensure long-term sustainability.